Gender asymmetries, parenthood and confinement in two portuguese prisons - Cunha, Manuela Ivone P. da (2014)
Parenthood is a gendered relation, but its bearing on how men and women “do” gender differs: fatherhood is more peripheral an attribute in men’s conventional gender definitions than motherhood is in women’s. Confinement situations may amplify this asymmetry. However, as prisons reflect structural variations, the very saliency of gender as a category of identity may be highly contextual. Drawing on fieldwork conducted in different periods in Portuguese carceral settings, we will focus on variable aspects of motherhood and forms of relatedness in different imprisonment situations.